Accumulation of Postoperative Unexpected Events Assessed by the Comprehensive Complication Index® as Prognostic Outcome Parameters for Kasai Procedure - Omid Madadi-Sanjani; Julia Brendel; Marie Uecker; Eva-Doreen Pfister; Ulrich Baumann; Johanna Ohlendorf; Joachim F. Kuebler (MDPI AG, 2022)
Introduction The Kasai procedure in children with biliary atresia (BA) is associated with several complications in the short-term. The Comprehensive Complication Index (CCI®) is a validated metric in adult surgery for the analysis of complications and morbidity in surgical patients. We aimed to analyze the CCI® for the first time in BA infants and to correlate its association with outcomes. Material and Methods We conducted a retrospective review of medical records of infants with type III BA undergoing the Kasai procedure between January 2011 and December 2021 at our institution. All unexpected events were ranked according to the Clavien-Dindo classification, and the CCI® per patient was subsequently calculated. Clavien-Dindo grades, individual events, CCI®, and total event numbers per patient were correlated with one- and two-year outcomes post-surgery. Results A total of 131 events were identified in 101 patients (ranging 0-11 per patient). Forty-four Grade I (33.6%), 67 Grade II (51.1%), 18 Grade III (13.7%), and two sentinel events [>Grade IV] (1.5%) were documented according to Clavien-Dindo, including one death in a cardiac-associated BA patient. None of the complications significantly correlated with a poor outcome. Sixty-three (62.4%) CCI® scores were calculated (range 0-100). The mean CCI® score during the in-patient treatment post-surgery was significantly higher in patients with a poorer outcome than patients with native liver survival at one- and two-year follow-up (22.7 ± 21.7 vs. 13.2 ± 18.1; p = 0.02). Conclusion Not the severity of complications, but the accumulation of numerous events related to Kasai procedure were associated with a poorer outcome. Therefore, the CCI® is an excellent instrument for the postoperative morbidity assessment of BA patients.